Coleridge’s Ecumenical Spinoza - Halmi, Nicholas (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
Of English writers of the early nineteenth century, none has so sustained and well-documented an engagement with Spinozan metaphysics as Coleridge. Encountering Spinoza's monism both indirectly, through works contributing to the pantheism controversy of the 1790s, and directly, in intensive study of a collected edition of Spinoza's works in 1812-13, Coleridge repeatedly identified the Dutch philosopher with Christianity, particularly in his personal conduct, while deploring the moral implications of his supposed denial of free will. This ambivalent response to Spinoza is reflective of a fundamental and persistent tension in Coleridge's own thought between his attraction to a metaphysical monism, as the basis for postulating the unity of subject and object, and his desire to affirm Trinitarian Christianity.